Wireless Sensor Network Design Using Multihop Based on Arduino and NRF24L01+ - Mochamad Faris Kurniawan; Riza Alfita; Miftachul Ulum; Hanifudin Sukri (Procedia of Engineering and Life Science, 2021)
The development of communication networks is very useful in daily activities such as wireless data communication, monitoring and system security. In this case, a wireless sensor network technology is known, which is very suitable when applied to a system with a large number of nodes and spread over a large enough area at a low cost. This wireless sensor network is a wireless communication network that supports communication between sensor nodes in a considerable distance by placing several sensors in an area. Generally, this Wsn consists of a sensor node and a server node in the form of a personal computer. The data from the reading of the CO gas value will be sent directly from the sensor node to the node server. This device is built using the nRF24L01 module and the CO gas sensor using the MQ-7 sensor. This wireless sensor network communication system is built using multihop. From the activities it can be concluded that the success of sending data is influenced by the distance and number of nodes working on a topology, with the amount of data sent which is influenced by long distances and the large number of nodes, not all data is successfully received because of the large number of data collisions from each node.